Multimodality cardiovascular imaging in pulmonary embolism - Kim, Hyung Yoon (Cardiol J, 2021)
Acute pulmonary embolism (APE) is one of the leading causes of cardiovascular (CV) morbidity and mortality. To select appropriate therapeutic strategy and/or to minimize the mortality and morbidity, rapid and correct identification of life-threatening APE is very important. Also, right ventricular (RV) failure usually precedes acute hemodynamic compromise or death, and thus the identification of RV failure is another important step in risk stratification or treatment of APE. With advances in diagnosis and treatment, the prognosis of APE has been dramatically improving in most cases, but inadequate therapy or recurrent episodes of pulmonary embolism (PE) may result in negative outcomes or, so called, chronic thromboembolic pulmonary hypertension (CTEPH). CTEPH is a condition characterized by remaining chronic thromboembolic material in the pulmonary vasculature and subsequent chronic pulmonary hypertension. Various imaging modalities include chest computed tomography pulmonary angiography (CTPA), echocardiography, magnetic resonance imaging, and nuclear imaging and each are used for the assessment of varying status of PE. Assessment of thromboembolic burden by chest CTPA is the first step in the diagnosis of PE. Hemodynamic assessment can be achieved by echocardiography and also by chest CTPA. Nuclear imaging is useful in discriminating CTEPH from APE. Better perspectives on diagnosis, risk stratification and decision making in PE can be provided by combining multimodality CV imaging. Here, the advantages or pitfalls of each imaging modality in diagnosis, risk stratification, or management of PE will be discussed.